The World Health Organization global aDSM database: generating evidence on the safety of new treatment regimens for drug-resistant tuberculosis. Issue 3 (22nd March 2018) - Halleux, Christine M.; Falzon, Dennis; Merle, Corinne; Jaramillo, Ernesto; Mirzayev, Fuad; Olliaro, Piero; Weyer, Karin
Marketing new medicines before pre-registration clinical trials are complete may sound rash and risky. But when treatment options are scarce in the face of a lethal, transmissible disease the balance tilts in favour of "use" rather than "wait". Such were the conditions under which bedaquiline and delamanid (two new tuberculosis (TB) agents) were introduced a few years ago. This article relates how uncertainties about the safety of these new drugs were handled to enable their use. The World Health Organization has created a central database to improve knowledge on drug-related harms of patients on novel tuberculosis regimens http://ow.ly/lfVm30ihRcO